Peran Hukum Internasional Dalam Resolusi Konflik Dan Perdamaian Dunia - Mawene, Marcha Jeanne; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
This study examines the role of international law in conflict resolution and the establishment of global peace, highlighting the effectiveness of legal mechanisms and the challenges of their implementation in prolonged conflict areas. Using a normative juridical approach, the research analyzes international legal instruments such as the UN Charter, the Geneva Conventions, and the Rome Statute, while also exploring their application in contemporary cases like the Russia–Ukraine conflict and the Israel–Palestine crisis. The findings indicate that international law holds a strategic position in providing a normative foundation for peaceful dispute settlement and accountability for human rights violations. However, its effectiveness is often hindered by the political interests of major powers, weak enforcement mechanisms, and the involvement of non-state actors in armed conflicts. Therefore, a strong global commitment, institutional reform, and enhanced legal frameworks are required to optimize the role of international law in achieving sustainable peace.